IMPLEMENTASI PROGRAM JARING (JANGKAU, SINERGI, DAN GUIDELINE) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT NELAYAN DI PROVINSI LAMPUNG TAHUN 2016 - administratio Department; Serli Ani; Eko Budi Sulistio (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This study attempts to describe how have program net program in theLampung. This research supported by the natural environment erratic, the level ofeducation fishermen low, the life patterns of the fishermen, marketing are caught. Thisresearch is used Van Meter and Van Horn’s approach of implementation model whichconsist of Standard and Policy Goals, Resources, Relationship Among The Organizations,Characteristics of Implementer Agent, Condition of Social, Economic and Politic andDisposition of Implementer. The method used in this research is descriptive qualitative.Furthermore, to see the utilization of the regulation, the research applies triangulationtechnique. The result is that the net program has been quite effective though there werea little obstacles and problem in practice. Using approach van meters and van horn, it canbe analyzed that the implementation of net program has been running as determined,although there are still some indicator not based on the situation on the ground. It tookhis policy standard clearer and detailed, it needs the increase in human resources andfinancial, it needs the expansion, should be made the communication and dialoguebetween stakeholders and fishermen or community representatives community leaders todeprive isue negative about net program. Keywords: implementation, net programs, welfare, a fishing community